2019
DOI: 10.1136/bmjopen-2018-023756
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining intention to leave among physicians in tertiary hospitals in China: a national cross-sectional study

Abstract: ObjectiveThe reasons that physicians leave the institutions have not been extensively studied. We aimed to evaluate these reasons, which include the desire to work at another hospital or the intention to make a career change, among physicians in tertiary hospitals in China and explore the associations between the individual-level and organizational-level factors related to these two reasons for leaving.MethodsWe conducted a national survey of 136 tertiary hospitals across all 31 provinces in China between Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 40 publications
2
37
1
2
Order By: Relevance
“…The association between low job satisfaction and intention to leave the profession has been described in several studies, both for physicians [2][3][4][5][6] and nurses [15][16][17][18][19][20][21]43]. A recent study on physicians in Saxony found an association between low job satisfaction and the tendency to move to other health systems [44].…”
Section: Step Likert Scalementioning
confidence: 95%
See 2 more Smart Citations
“…The association between low job satisfaction and intention to leave the profession has been described in several studies, both for physicians [2][3][4][5][6] and nurses [15][16][17][18][19][20][21]43]. A recent study on physicians in Saxony found an association between low job satisfaction and the tendency to move to other health systems [44].…”
Section: Step Likert Scalementioning
confidence: 95%
“…The effect of perceived quality of care on intention to leave the profession was partially mediated by job satisfaction. Thus, high perceived quality of care and high job satisfaction are both important factors that tend to prevent young physicians and nurses from leaving their professions.for this include overtime, psychosocial stress, burnout, career aspects and particularly, a low level of job satisfaction [2][3][4][5][6]. In order to improve their balance between work and family, some physicians switch to nontherapeutic work or emigrate, in the hope of finding better working conditions in other countries [7].Although the absolute number of all physicians in Germany has been constantly increasing over the years [8], it is still justified to discuss a "relative lack of physicians" or a "lack of medical working hours".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This overload situation and inability to effectively administer optimal patient care, can cause stress and burnout, thereby prompting physicians to consider leaving the profession [ 26 , 32 , 47 ]. Physician shortages have become a pervasive issue worldwide [ 48 ]. Given the significant shortage of physicians and since exit from the profession due to burnout is one of the primary reasons in this regard [ 32 ], it apposite to examine intention to leave the profession as a withdrawal mechanism from experienced burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to providing specialist mental health services for larger geographical areas than SPHs, TPHs are also responsible for providing guidance and support to all other mental health service providers, including SPHs, in the corresponding areas [12]. Therefore, Chinese psychiatrists working at TPHs are often burdened with much heavier workloads and faced with an even grimmer crisis of burnout [13,14]. Considering the central roles that TPHs play in China's mental health care system, more attention should be focused on burnout and job dissatisfaction among psychiatrists working at TPHs in China.…”
Section: Introductionmentioning
confidence: 99%